Analysis of food waste behavior by muslim generation Z through online food delivery - Mariyah, Meliani Siti; Arsyianti, Laily Dwi; Aurahma, Adora (Halal Studies and Society, 2024)
In recent years, there has been a consistent annual increase in the prevalence of food waste, which negatively affects the economy of various countries, such as Indonesia. Previous studies showed that food waste in Indonesia reached 41.4% of the total composition of national waste in 2021. This increase is accompanied by technological developments that affect consumption patterns, such as online food delivery (OFD) services. Therefore, this study aims to analyze food waste behavior among Muslim Generation Z through OFD in West Java using the Theory of Planned Behavior (TPB). Primary data were obtained from 180 participants and analyzed using the Structural Equation Modeling- Partial Least Square (SEM-PLS). The results showed that there was a significant positive relationship between the attitude variable and perceived behavior control with intention, while the subjective norms variable had no effect. A significant positive relationship was also obtained between promotion, OFD, and perceived behavior control with food waste behavior. Meanwhile, intention and OFD had no significant effect.